Human retroviral host restriction factors APOBEC3G and APOBEC3F localize to mRNA processing bodies. - Michael J Wichroski (Public Library of Science (PLoS), 2006)
APOBEC3G is an antiviral host factor capable of inhibiting the replication of both exogenous and endogenous retroviruses as well as hepatitis B, a DNA virus that replicates through an RNA intermediate. To gain insight into the mechanism whereby APOBEC3G restricts retroviral replication, we investigated the subcellular localization of the protein. Herein, we report that APOBEC3G localizes to mRNA processing (P) bodies, cytoplasmic compartments involved in the degradation and storage of nontranslating mRNAs. Biochemical analysis revealed that APOBEC3G localizes to a ribonucleoprotein complex with other P-body proteins which have established roles in cap-dependent translation (eIF4E and eIF4E-T), translation suppression (RCK/p54), RNA interference-mediated post-transcriptional gene silencing (AGO2), and decapping of mRNA (DCP2). Similar analysis with other APOBEC3 family members revealed a potential link between the localization of APOBEC3G and APOBEC3F to a common ribonucleoprotein complex and P-bodies with potent anti-HIV-1 activity. In addition, we present evidence suggesting that an important role for HIV-1 Vif, which subverts both APOBEC3G and APOBEC3F antiviral function by inducing their degradation, could be to selectively remove these proteins from and/or restrict their localization to P-bodies. Taken together, the results of this study reveal a novel link between innate immunity against retroviruses and P-bodies suggesting that APOBEC3G and APOBEC3F could function in the context of P-bodies to restrict HIV-1 replication.